Improving the Machining Process of the Metalworking Industry Using the Lean Tool SMED - Monteiro, Carlos (2020)
The project here presented was developed in a metalworking company, where several areas requiring improvement were identified. The study addresses the elimination of waste and increase of productivity in the machining sector of the company. To this purpose key processes were identified and mapped using flowcharts and VSM (Value Stream Mapping). Achieved improvements involved decreasing setup times by resorting to the lean tool SMED (Single Minute Exchange of Die). Setup times were reduced in 40% on the vertical milling machine of the company, and in 57% on the horizontal milling machine.